Clinical Characteristics of Systemic Sclerosis With Interstitial Lung Disease - Eunju JUNG; Chang-hee SUH; Hyoun-ah KİM and Ju-yang JUNG (Archives of Rheumatology, 2018)
Objectives: This study aims to compare the clinical characteristics of systemic sclerosis (SSc) patients with or without interstitial lung disease (ILD), and figure out whether the differences can be useful to suspect ILD in SSc. Patients and methods: We retrospectively collected the clinical data of 108 patients with SSc (13 males, 95 females; mean age 50.1±13.5 years; range 14 to 78 years) and compared them according to the presence of ILD. ILD was confirmed by chest computed tomography, and pulmonary arterial hypertension was suspected when right ventricular systolic pressure was ≥40 mmHg based on echocardiography. Results: Of the 108 patients, 49 (45.4) had diffuse type and 59 (54.6) had limited type SSc. Disease duration, percentages of positive anti-scleroderma 70 (anti-Scl70) antibody and anti-centromere antibody, white blood cell, platelet, erythrocyte sedimentation rate (ESR), and presence of pulmonary hypertension differed significantly. On multivariate logistic analysis, positive titer of anti-Scl70 antibody (odds ratio [OR]=15.65, p<0.001), platelet (OR=1.01, p=0.026), ESR (OR=1.02, p=0.037) and pulmonary hypertension (OR=21.97, p=0.003) were associated with ILD in patients with SSc. Conclusion: In SSc patients with ILD, disease duration was longer and positive titer of anti-Scl70 antibody was more frequent, positive titer of anti- centromere antibody was less frequent, and white blood cell and platelet counts, ESR levels, and incidence of possible pulmonary hypertension were significantly higher than in those without ILD. Positive titer of anti-Scl70 antibody, platelet, ESR, and combination of pulmonary hypertension were independently associated with the presence of ILD in SSc patients.